Histories of global inequality new perspectives - Christiansen, Christian Olaf 1980-; Jensen, Steven L. B. 1973- (Palgrave Macmillan, 2019)
This book argues that inequality is not just about numbers, but is also about lived, historical experience. It supplements economic research and offers a comprehensive stocktaking of existing thinking on global inequality and its historical development. The book is interdisciplinary, drawing upon regional and national perspectives from around the world while seeking to capture the multidimensionality and multi-causality of global inequalities. Grappling with what economics offers – as well as its blind spots – the study focuses on some of today’s most relevant and pressing themes: discrimination and human rights, defences and critiques of inequality in history, decolonization, international organizations, gender theory, the history of quantification of inequality and the history of economic thought. The historical case studies featured respond to the need for wider historical research and to calls to examine global inequality in a more holistic manner.The Introduction 'Chapter 1 Histories of Global Inequality: Introduction' is open access under a CC BY 4.0 license via link.springer.com